Kecanduan Media Sosial pada Generasi Z dalam Perspektif Al-Qur’an: Analisis Tematik Konsep Khusr, Laghw, dan Lahw - Alwi Gorga Doli Harahap; Mardian Idris Harahap (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study examines social media addiction among Generation Z from the perspective of the Qur’an by focusing on the concepts of khusr, laghw, and lahw. The development of social media has facilitated communication and access to information; however, excessive use may encourage compulsive behavior, time wasting, procrastination, purposeless content consumption, and reduced attention to more productive and meaningful activities. This study employs a qualitative method using library research and a thematic Qur’anic interpretation (maudhu‘i) approach. The primary data consist of Qur’anic verses related to the concepts of khusr, laghw, and lahw, while secondary data are drawn from Qur’anic commentaries, books, journal articles, and previous studies on social media addiction among Generation Z. The data are analyzed descriptively and analytically by relating the meanings of the verses and the interpretations of Qur’anic scholars to the contemporary phenomenon of social media use. The findings indicate that social media addiction can be understood through three Qur’anic dimensions. The concept of khusr represents loss resulting from wasting time and missing opportunities to engage in meaningful activities. The concept of laghw refers to involvement in activities that provide little or no meaningful benefit, including excessive social media use without a clear purpose. Meanwhile, lahw represents forms of entertainment and pleasure that may distract individuals from their life purposes and responsibilities. These three concepts demonstrate that the fundamental problem of social media addiction does not merely lie in the use of technology itself, but in the loss of control over time, purpose, and life orientation. Therefore, the Qur’anic perspective provides an ethical framework for Generation Z to use social media proportionally, productively, and responsibly.